2019
DOI: 10.1007/s11071-019-05391-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis and performance evaluation of nonlinear inerter-based vibration isolators

Abstract: This paper investigates a nonlinear inertance mechanism (NIM) for vibration mitigation and evaluates the performance of nonlinear vibration isolators employing such mechanism. The NIM comprises a pair of oblique inerters with one common hinged terminal and the other terminals fixed. The addition of the NIM to a linear spring-damper isolator and to nonlinear quasizero-stiffness (QZS) isolators is considered. The harmonic balance method is used to derive the steadystate frequency-response relationship and force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…The fluid inerter has superior application potential because of its simpler design and high impact resistance. As a common hydraulic drive system, the nonlinearity factors of fluid inerter cannot be ignored [21][22]. In [23], Akkaya proposed that in the analysis and design of the hydraulic transmission control system, the oil bulk modulus should be considered as a variable parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid inerter has superior application potential because of its simpler design and high impact resistance. As a common hydraulic drive system, the nonlinearity factors of fluid inerter cannot be ignored [21][22]. In [23], Akkaya proposed that in the analysis and design of the hydraulic transmission control system, the oil bulk modulus should be considered as a variable parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the inerter concept, it has been applied to aircraft landing gear shimmy suppression [8], vehicle suspension systems [9] and building vibration control system [10]. Some studies have also been reported on the performance of inerter-based single degree-of-freedom (DOF) vibration isolators [11], dual-stage isolator [12] and nonlinear inerter-based isolator [13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its mechanical property, the inerter has been observed as an efficient vibration attenuation device whose benefits are shown in many structures, for instance, vehicle suspensions, [13][14][15] train suspensions, 16 tuned mass dampers, [17][18][19][20] building vibration control systems, [21][22][23][24][25] landing gears, 26 nonlinear energy sinks, 27,28 and vibration isolators. [29][30][31][32][33][34][35] Here, the inerter applied in the vibration isolators is especially concerned. Hu et al 29 analyzed the dynamic performance for five kinds of vibration isolator using inerter, indicated that it could have a smaller transmissibility than the common linear one consists of damper and spring.…”
mentioning
confidence: 99%
“…Wang et al 34 further analyzed the isolation performance of this vibration isolator and found that the force transmissibility is smaller, and the isolation frequency band is wider than those of the linear one. Yang et al 35 proposed a nonlinear inertance mechanism, applied it in the linear and nonlinear vibration isolators, and found that it could have an advantageous effect for vibration attenuation.…”
mentioning
confidence: 99%
See 1 more Smart Citation